Старые письма: [роман] / Даниэла Стил ; перевод с английского Е. В. Погосян - Стил Даниэла (АСТ, 2000)
Экземпляры: аб. ЦБ (20200917) / Инвентарный номер: 9722 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: С 80 / ББК: 84(7Сое)